HIV risks and recent HIV testing among transgender women in Cambodia: Findings from a national survey - Sok, Say (PLoS One, 2020)
BACKGROUND: Globally, the prevalence of HIV among transgender women remains much higher than that of the general population, and a large proportion of them are unaware of their HIV status. Transgender women are exposed to gender-based violence and social stigma and discrimination in different settings that may create significant barriers to receiving HIV prevention and care services. This study aimed to identify factors associated with recent HIV testing among transgender women in Cambodia. METHODS: We conducted a cross-sectional survey in 2016 among 1375 transgender women recruited from 13 provinces using a peer-based social network recruitment method. We used a structured questionnaire for face-to-face interviews and performed rapid HIV/syphilis testing onsite. We used a multiple logistic regression analysis to identify factors associated with recent HIV testing. RESULTS: Of the total, 49.2% of the participants reported having an HIV test in the past six months. After controlling for other covariates, the odds of having an HIV test in the past six months was significantly lower among students (AOR 0.36, 95% CI 0.20–0.65), participants who perceived that they were unlikely to be HIV infected (AOR 0.50, 95% CI 0.32–0.78), and participants who reported always using condoms with male non-commercial partners in the past three months (AOR 0.65, 95% CI 0.49–0.85) relative to their respective reference group. The odds of having an HIV test in the past six months was significantly higher among participants who had been reached by community-based HIV services (AOR 5.01, 95% CI 3.29–7.65) and received HIV education (AOR 1.65, 95% CI 1.06–2.58) in the past six months relative to their respective reference group. CONCLUSIONS: Despite the widely available free HIV testing services, more than half of transgender women in this study had not received an HIV test in the past six months. Our findings suggest that a tailored and comprehensive combination prevention program, in which HIV testing is linked to care continuum and beyond, maybe an essential next step. Social media may have the potential to be promoted and utilized among transgender women populations in order to improve HIV testing and other prevention measures.